Review of Current Strategies to Address Micronutrient Deficiencies (MNDs) in Ghana: A Scoping Review - Jolene Mateko Azagba-Nyako; Charles Tortoe; Paa Toah Akonor; Alice Padi; Jackline Boateng; Richard Otwey (Journal of Nutrition and Metabolism)
To achieve the Sustainable Development Goals by 2030, low-income countries like Ghana will require strategizing towards sustainable reduction in micronutrient deficiency (MND) diseases and MND-related morbidity and mortality. A scoping review was conducted to identify the policy framework around MND intervention, the actors implementing MND-related strategies and documented evidence on which strategies worked across implementation stakeholders. Forty-six peer-reviewed articles were selected (n = 46) including studies on nutrition-sensitive intervention studies (n = 15) and nutrition-specific intervention (n = 31). Eligibility criteria for inclusion of information from articles and publications were based on report findings on nutrition-related programmes and policies conducted and implemented in Ghana and should have been published between 2000 and 2024. Databases adopted for this scoping review include Google Scholar, PubMed, ScienceDirect, AGORA, Hinari and JSTOR. This scoping review obtained a comprehensive picture of the nutrition situation in Ghana by gathering nutrition surveillance data depicting the different strategies employed to combat MNDs in Ghana. The scoping review identified several MND intervention strategies; however, the sustainability of the strategies required effective implementation guidelines, policies and programmes that address dietary deficits specific to a particular population.